Refluxing Versus Non-Refluxing Uretero-Vesical Anastomosis in Renal Transplant - Mushtaq Ahmad, Nasrum Minallah, Ahmad Nawaz, Akhtar Nawaz, Tariq Ahmad, Ikram Ullah Khattak, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Urinary tract infection and pyelonephritis are very common in patients with renal transplant. One of mechanism to prevent pyelonephritis is performing a non-refluxing anastomosis of ureter with bladder. Whether this procedure can decrease the rate of urinary tract infection and pyelonephritis is controversial. Objective: To assess the out-come of refluxing versus non-refluxing ureterovesical anastomosis in renal transplant recipients. Study Design: Randomized Control Trial (RCT) Methodology: This RCT was carried out in the Department of Urology and Renal Transplant, Institute of Kidney Diseases Hayatabad Medical Complex Peshawar from January 2015 to January 2020. A total of 52 patients who underwent live donor renal transplant were equally divided into two groups by block randomization, Group A-refluxing and Group B-non-refluxing ureterovesical anastomosis. Informed written consent was obtained from all patients. Each patient was followed for a period of one year and outcome parameters including frequency of anastomotic leakage, anastomotic stenosis, symptomatic UTI, hematuria and mean nadir creatinine level were recorded. The data were analyzed using SPSS version 26 using chi-square test for categorical data and T-test for numerical data keeping p-value < 0.05 as significant. Results: The mean age in group A and group B was 36.6 + 6.1 and 35 + 4.7 years respectively (p-value > 0.05). In group A, no patient developed anastomotic stenosis whereas in group B, 2 (7.7 %) patient developed anastomotic stenosis (p-value > 0.05). 1 (3.8 %) patient in group A developed anastomotic leakage while none of the patients in group B developed any leakage (p-value > 0.05). The mean nadir serum creatinine in group A was 1.3 + 0.4 mg/dl and 1.2 + 0.2 mg/dl in group B (p-value > 0.05). 4 (15.4%) of patients in group A and 3 (11.5%) of the patients in group B developed UTI (p-value > 0.05). Practical Implication: The refluxing ureterovesical anastomosis is relatively easier and less time consuming in comparison to the non-refluxing technique, since there is no statistical difference between their outcomes, the refluxing technique can be utilized in adult kidney transplant recipients. Conclusion: We concluded from this study that there is no statistically significant difference in the out-come between refluxing and non-refluxing ureterovesical anastomosis in renal transplant patients of adult age. Keywords: Lich-Gregoire, Renal Transplantation, Refluxing Ureterovesical anastomosis, Urine Leakage, UTI